Sensor networks with multiple technologies: short and long range - Oliveira, Rúben Pedrosa (2018)
Low-Power Wide Area Networks (LPWANs) are one set of technologies that are growing in the eld of the Internet of Things (IoT). Due to the long range capabilities and low energy consumption, Low-Power Wide Area Networks (LPWANs) are the ideal technologies to send small data occasionally. With their unique characteristics, LPWANs can be used in many applications and in di erent environments such as urban, rural and even indoor. The work developed in this dissertation presents a study on the LPWAN LoRa technology, by testing and evaluate its range, signal quality properties and its performance in delivering data. For this, three distinct scenarios are proposed and tested. The inclusion of LoRa in a multi-technology data gathering platform is the key objective of this dissertation. For this it is proposed: (1) an organization based in clusters of sensor nodes; (2) a Media Access Control (MAC) protocol to provide e cient communications through the LoRa technology; and nally, (3) a Connection Manager that is capable of managing the di erent available technologies in the sensor nodes and that is able to adapt its actions according to the acquired data type is proposed. The performed tests aim to perceive which type of parameters can in uence the performance of the overall proposed solution, as well as the advantages of a multi-technology approach in a data gathering platform.